Exploring application of e-tendering in Malaysian construction industry during covid-19 pandemic - Tan, Yee Ying (2022)
Beginning in 2020, Malaysia declared a lockdown policy to restrict the spread of the Covid-19 virus. As everyone needed to work from home, the traditional tendering method was impossible to be carried out. Thus, the e-tendering system was used instead during this period. Previous research has mostly focused on implementing an e-tendering system and the effects of Covid-19 on the construction sector. However, there has been little research into how the tendering process was carried out during the Covid-19 pandemic. As a result, this study investigated the various tendering methods used in the Malaysian construction industry before and during the Covid-19 outbreak. This research also studied the critical success factors and obstacles of applying an e-tendering system in the Malaysian construction industry. The quantitative research method was used to collect data via the questionnaire survey. The data was collected from 99 quantity surveyors who are working in the Malaysian construction industry. The findings revealed that the traditional tendering method was mostly used before the Covid-19 pandemic, while the e-tendering system and email were used to conduct tendering processes during the Covid19 pandemic. The five strongly agreed critical success factors of e-tendering system application were revealed as (1) reduce printing cost; (2) avoid crowd gathering; (3) avoid physical contact; (4) reduce physical storage; and (5) reduce time on duplicating tender documents. Lack of knowledge was a significant obstacle perceived by the quantity surveyors whose companies did apply the etendering system. Besides, the quantity surveyor whose companies did not apply the e-tendering system perceived the high initial cost to purchase software as the most significant obstacle. This research also carried out the inferential test and found significant differences between the respondent groups regarding the critical success factors and obstacles of e-tendering system application. According to the findings of this research, fewer construction firms were using the e-tendering system throughout the tendering process. It also outlined the trend of adopting an e-tendering system before and during the Covid-19 pandemic in the Malaysian construction industry. This research provided insights and awareness to the construction professionals on the importance of implementing the e-tendering system.